2014
DOI: 10.1093/bja/aeu016
|View full text |Cite
|
Sign up to set email alerts
|

Burst suppression-MAC and burst suppression-CP50 as measures of cerebral effects of anaesthetics

Abstract: Immobility and cerebral effects reflect different entities of anaesthetic action. The median concentration of anaesthetic drug (volatile or i.v. agent) required to induce 'silent second' might be a more useful metric than the median concentration required to prevent movement in response to a surgical stimulus in order to compare relative potencies of anaesthetic agents on the brain. Advantage of the 'silent second' is an easy identification of this endpoint, while such a deep level is not required for clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 51 publications
2
26
2
2
Order By: Relevance
“…This contrasts with data from neonatal rodent studies, which suggest that isoflurane and sevoflurane increase neuronal cortical activity leading to seizure like EEG patterns [11, 69]. In both our piglet and previous macaque studies [13] there is considerably less cell death than that seen in rodents following a similar exposure to isoflurane, which may be partly explained by the absence of seizure activity.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with data from neonatal rodent studies, which suggest that isoflurane and sevoflurane increase neuronal cortical activity leading to seizure like EEG patterns [11, 69]. In both our piglet and previous macaque studies [13] there is considerably less cell death than that seen in rodents following a similar exposure to isoflurane, which may be partly explained by the absence of seizure activity.…”
Section: Discussioncontrasting
confidence: 99%
“…In humans, low doses of sevoflurane increase beta/low gamma power in the frontal EEG (Gugino et al, 2001; Brown et al, 2010), and higher doses increase slow-delta and alpha power (Akeju et al, 2014; Purdon et al, 2015) and induce burst suppression (Pilge et al, 2014). Loss of consciousness in humans under sevoflurane and propofol anesthesia is associated with an increase in slow-delta power in the frontal EEG (Gugino et al, 2001; Purdon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis a variety of efforts have been made to estimate the concentration dependent emergence of burst suppression during anesthesia. It has been found that during sole agent isoflurane anesthesia, the burst suppression pattern can emerge at end-tidal concentrations as low as 1.2% (Hoffman and Edelman, 1995; Pilge et al, 2014), i.e., aqueous concentrations of ≃ 0.25 mM at 37°C. However when arterial blood concentrations of isoflurane have been measured the onset of burst suppression has been reported for levels as low as 34.9 μg/ml or ≃ 0.19 mM (Loomis et al, 1986) – close to the value at which we observed the onset of burst suppression in our model.…”
Section: Discussionmentioning
confidence: 99%